Plyometrics
Plyometrics is a fancy name for "jumping drills." The point of plyos is to train the nervous system and muscles to execute the full jumping motion with as much coordination, power, and speed as possible. In practice, this means you should concentrate on jumping quickly, "bouncing" off the ground (rather than "pushing" off the ground) while maintaining a full range of motion. By the way, plyometrics work. As you do the drills below, focus on jumping with a full range of motion the instant before you plant your feet to jump -- that is, punch your feet into the floor like a gymnast instead of planting, then squatting, then jumping. Also, use a long, explosive, double-arm swing every single time you jump, with your fully-extended arms traveling through a nearly 180 degree range of motion. You probably find this easy to do during a regular approach jump, but most players do it poorly (or not at all) when hopping, bounding, and depth-jumping . . . which is precisely why they need to practice it. In game situations, hitters often have to jump without taking the "perfect" approach; in those situations, their bodies must automatically jump correctly. Forcing them to use double-arm swings in awkward jumping drills increases the likelihood of them using good jumping mechanics when they're off-balance or out of position in a game. For your plyometric workouts, keep things short and simple. After an excellent warmup, you can do one of the following workouts. These workouts, which take only about 15 minutes to complete, should immediately precede your weight workout two days a week during the offseason, one day a week during the season. (To see a video clip of each drill, click on the drill's name. The clips range from 200k to 500k, so be patient.) "High Impact" Plyometric Workout (approximately 150 foot contacts) 5 20m Bunny Hops or Zig-Zag Bunny Hops 5 20m Bounding (L, R, L, R, L, R, . . .) or Hopping (L, L, L, . . .) 5 x 5 Zig-zag Plants (final two steps of approach, angling to the right, then left, then right, etc.) 5 x 5 Depth Jumps (using a set of stable jumping boxes) Block Jumps to failure (one continuous set until you're jumping no higher than six inches) "Low Impact" Plyometric Workout (approximately 160 foot contacts) 3 x 12 Square Jumps I (jump from corner to corner on a 4'-5' square) 3 x 12 Square Jumps II (jump from corner to corner on a 4'-5' square) 3 x 15 Explosive Step-Ups (step up on a jumping box and explode into the air) 3 x 15 Box Jumps (jump up on to box, step off, pause, repeat)